The Influence of Entrepreneurial Spirit, Family Environment and Internal Locus of Control on Entrepreneurial Interest - Widya Safitri; Nurasik Nurasik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the influence of the entrepreneurial spirit, family environment and internal locus of control on entrepreneurial interest. The sampling method used is probability sampling. The probability sampling technique used in this study is the Slovin formula. The sample in this study were 257 respondents. The data used is primary data. The data analysis method used in this study is Multiple Linear Regression with SPSS 25. The results of this study indicate that the entrepreneurial spirit has an influence on entrepreneurial interest. Family Environment Affects Interest in Entrepreneurship. Internal Locus of Control Affects Entrepreneurial Interest